Assessment of Preservice Music Teachers’ Multicultural Personality: Multicultural Music Education Perspective - Chen, Shu; Wong, Kwan Yie (Frontiers in Psychology, 2022)
This study examines preservice music teachers’ multicultural personality level and characteristics in the context of multicultural music education in China, focusing on the factors that influence the teachers’ multicultural personality traits. We surveyed 433 preservice music teachers who responded via the Multicultural Personality Questionnaire-Short Form survey instrument. The results indicated that the multicultural personality level of preservice music teachers was intermediate, mainly due to a deficiency in the Flexibility and Emotional Stability dimensions, which are necessary for dealing with cultural differences in the face of unknown multicultural conditions. In addition, we also found that the size of a teacher’s hometown and the years of studying and teaching are significant factors in shaping preservice music teachers’ multicultural personalities. Preservice music teachers whose hometowns are big cities have a higher multicultural personality level than those in rural areas. The more time a preservice music teacher spent studying and teaching, the higher the multicultural personality level. Gender, educational level, and experience playing musical instruments have no statistically significant effect on the multicultural personality of preservice music teachers.